2008
DOI: 10.1007/s10661-008-0346-y
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of insects and insectivorous birds to metals and other elements from abandoned mine tailings in three Summit County drainages, Colorado

Abstract: Concentrations of 31 metals, metalloids, and other elements were measured in insects and insectivorous bird tissues from three drainages with different geochemistry and mining histories in Summit Co., Colorado, in 2003, 2004, and 2005. In insect samples, all 25 elements that were analyzed in all years increased in both Snake and Deer Creeks in the mining impacted areas compared to areas above and below the mining impacted areas. This distribution of elements was predicted from known or expected sediment contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…In contrast to using tissue samples, analysis of bird feces is a non-invasive non-destructive procedure, which allows the assessment of exposure to environmental metallic contaminants with minimal stress to individuals and populations, an imperative prerequisite in the case of endangered and protected species (Fitzner et al, 1995;Fossi et al, 1999;Leonzio et al, 2009;Metcheva et al, 2011;Luo et al, 2013;Fu et al, 2014). Although a relationship between metal concentrations in the feces and accumulation in internal organs has not so far been widely established (Custer et al, 2009;Costa et al, 2012;Luo et al, 2013), significant correlations were found between Pb concentrations in excreta and concentrations in the liver and blood of greylag geese (Anser anser) (Mateo et al, 2006) whereas it was found possible to depict to at least some extent the potential accumulation of As, Cd and Pb in internal tissues of passerines using concentrations in the feces (Costa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to using tissue samples, analysis of bird feces is a non-invasive non-destructive procedure, which allows the assessment of exposure to environmental metallic contaminants with minimal stress to individuals and populations, an imperative prerequisite in the case of endangered and protected species (Fitzner et al, 1995;Fossi et al, 1999;Leonzio et al, 2009;Metcheva et al, 2011;Luo et al, 2013;Fu et al, 2014). Although a relationship between metal concentrations in the feces and accumulation in internal organs has not so far been widely established (Custer et al, 2009;Costa et al, 2012;Luo et al, 2013), significant correlations were found between Pb concentrations in excreta and concentrations in the liver and blood of greylag geese (Anser anser) (Mateo et al, 2006) whereas it was found possible to depict to at least some extent the potential accumulation of As, Cd and Pb in internal tissues of passerines using concentrations in the feces (Costa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As arsenic is a micronutrient for some vertebrates (Eisler 1988a), and as it is rapidly metabolized by birds (Pendleton et al 1995), it may not accumulate to toxic levels in tissues unless exposure is extreme (Custer et al 2009). However, Burger and Gochfeld (2009) The Spearman's Rho value is given in each box and the p value in brackets.…”
Section: Arsenicmentioning
confidence: 99%
“…In the case of Willow Grouse (Lagopus lagopus), Cd liver concentrations of approximately 10,000 ppb d-w were related to high metallothionein levels, indicating a physiological response to Cd exposure (Pedersen and Hylland 2007). A geometrical mean with various insectivorous birds considers 100 ppb d-w as background levels, since kidney samples did not reveal changes related to toxic cadmium levels (Custer et al 2009). Mean Cd values in livers from captive Ornate Tinamou showed very low concentrations, with both control sites situated within Scheuhammer's background levels, but at NP2, an individual reached 8,800 ppb d-w. At P1, the mean value for Ornate Tinamou was higher than 10,000 ppb d-w, and at both sites, several Ornate Tinamou individuals reached values higher than 20,000 ppb d-w, indicating a high Cd exposure in the field.…”
Section: Cadmiummentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies on copper element were mostly about its dissolution process and the influence on nature [7,8,[10][11][12][13][14][15][16][17][18][19]. In this paper, we discuss the distribution characteristic of copper in the mine tailing dam.…”
Section: Introductionmentioning
confidence: 99%